Occultism in the Renaissance - Mažeikis, Gintautas (Problemos, 1996)
The specific features of magic and occult philosophy in the Renaissance are analysed. For this aim the phenomenological conception of undifferentiated, magical aesthetic continuum of consciousness is introduced and the mythic, magical-symbolic, notional-analytic forms of thinking are distinguished there. The basic, dominating characteristics of the symbolic thinking of the Renaissance such as anthropocentrism, anthropomorphism, pantheism are considered. The magical, occult arts such as the natural magic, the hermetism, the art of memory, the Christian Cabala are discussed. The special attention is given to such philosophers as Nicholas of Cusa, Giordano Bruno, Heinrich Cornelius Agrippa, Robert Fludd.